Recent Advancements in Oral Anticoagulants: A Systematic Review - Sharma, Ram Kripal (Nepalese Medical Journal, 2022)
Anticoagulants are medications that are administered to patients with clotting issues. Major issues include atrial fibrillation, venous thromboembolism/deep vein thrombosis, and pulmonary embolism. However, recent studies show the increased use of these medications in the treatment and management of COVID-19. This paper has been designed as a systematic Literature review based on PRISMA strategy. Data were collected by conducting exhaustive research on major electronic databases i.e., SCOPUS, Web of Science, EMBASE, ProQuest, ScienceDirect, and Google Scholar. A total of 52 studies were included in this review. These studies were selected from the period 2011-2021. The overall study revealed the advancements of DOACs or NOACs in comparison to Warfarin, revealed the findings of various food, drug, and another kind of products that interfere with oral anticoagulants, and advancements in terms of treatment of DVT/VTE, pulmonary embolism, and arterial fibrillation by use of oral anticoagulants and the role of anticoagulation in COVID-19.